The design thinking process as an approach to facilitate problem-solving in piano repertoire - Smit, Marnel (Stellenbosch : Stellenbosch University, 2025)
Smit, Marnel. 2024. The design thinking process as an approach to facilitate problem-solving in piano repertoire. Unpublished masters dissertation. Stellenbosch : Stellenbosch University [online]. Available: https://scholar.sun.ac.za/handle/10019.1/131913